The protective effect of 17 β-estradiol on human uterosacral ligament fibroblasts from postmenopausal women with pelvic organ prolapse - Xie, Ting; Guo, Dan; Guo, Tao; Zhu, Yapei; Li, Fangyuan; Zhang, Sumei; Lang, Jinghe; Sun, Zhijing (Frontiers in Physiology, 2022)
This study aims to explore the protective effects of 17 β-estradiol on the human uterosacral ligament fibroblasts (hUSLFs) under static or stretched conditions. The experiments were performed on hUSLFs derived from pelvic organ prolapse (POP) and non-POP patients. Fibroblasts were cultured after collagenase digestion and identified by morphological observation and immunocytochemical methods. 17 β-estradiol (10 −10 M and 10 −9 M) and mechanical stress induced by the FX-5000 T-cell stress loading system under a loading strain of 1/2 sin waveform uniaxial cyclic stress with a tensile strain of 20% and a frequency of 0.5 Hz were either or both applied on hUSLFs. Cell proliferation was measured by CCK8, and cell apoptosis and death were detected using Annexin V/7-AAD staining and flow cytometric analysis. We found that the fibroblasts growth rate of POP patients was significantly lower than controls. The cell apoptosis and death rate increased as the mechanical load intensifying. After 20% mechanical stretching for 24 h, the dead cell rate was higher in POP than control. Notably, 17 β-estradiol treatment reversed mechanical stress induced hUSLFs apoptosis and death in both POP and Control cells. The protein and mRNA levels of anti-apoptotic PARP1 (poly-ADP-ribose polymerase) and Bcl-2 were increased by estrogen treatment. Meanwhile, expression of estrogen receptor α, a target of Poly-ADP-Ribosylation of PARP1, was also enhanced by 17 β-estradiol under the mechanical load. In conclusion, estrogen application ameliorates the mechanical strain induced cell apoptosis and death in hUSLFs from POP patients. PARP1 might be involved in this protective process, providing novel insights into the mechanical biology of and possible therapies for POP.